The Influence of Panda Kid’s Club Activities on Repeat Visit Intentions at Holiday Inn Resort, Batam City - Seffany, Diana; Lubis, Arina Luthfini (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
This study evaluates the impact of activities and facilities at Panda Kid’s Club at Holiday Inn Resort Batam City, on guests' intention to return. The research questions identified are how activities at Panda Kid’s Club influence guests' intention to return and how the provided facilities contribute to this effect. The main objectives of this research are to determine the impact of Panda Kid’s Club activities on return intentions and how its facilities affect them. The quantitative method is based on the approach described by (John W. Creswell, 2017) to measure quantitative data objectively through surveys. This study uses the SPSS version 23 application to process the research survey data. The results of the analysis indicate a positive impact of creative and educational activities and good and safe facilities on guests' intention to return. The conclusion of this study confirms that activities at Panda Kid’s Club significantly influence guests' intention to return. Recommendations for future research include expanding the scope by incorporating additional independent variables to gain a more comprehensive understanding of factors affecting return intentions.